Encyclopedia of crime and punishment - Levinson, David, 1947- (Thousand Oaks, Ca. : Sage Publications, 2002)
"Authoritative and comprehensive, this multivolume set includes hundreds of articles in the field of criminal justice. Impressive arrays of authors have contributed to this resource, addressing such diverse topics as racial profiling, money laundering, torture, prisoner literature, the KGB, and Sing Sing. Written in an accessible manner and attractively presented, the background discussions, definitions, and explanations of important issues and future trends are absorbing. Interesting sidebars and facts, reference lists, relevant court cases, tables, and black-and-white photographs supplement the entries. Appendixes cover careers in criminal justice, Web resources, and professional organizations. A lengthy bibliography lists relevant works."--"The Best of the Best Reference Sources," American Libraries, May 2003
v. 1. A-C -- v. 2. D-i -- v. 3. J-R -- v. 4. S-Z, Index
Includes bibliographical references and index
Keywords: Criminology -- Encyclopedias; Criminal justice, Administration of -- Encyclopedias